Disseminated tuberculosis in an infant – Case report - Abreu, Ana Margarida (2023)
Infants are a particularly vulnerable group for the development of severe and/or extrapulmonary forms of tuberculosis. The difficulty in establishing a definitive and timely diagnosis contributes to the high morbimortality in this age group. Investigation often relies on a high index of suspicion. Herein is reported a case of disseminated tuberculosis in an infant that highlights its clinical complexity and diagnostic challenge.